2007
DOI: 10.1063/1.2817741
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between compositional fluctuation and magnetic properties of Tm-doped AlGaN alloys

Abstract: The magnetic properties of Tm-doped AlxGa1−xN (0⩽x⩽1) alloys grown by solid-source molecular beam epitaxy were studied by hysteresis measurements and shown to exhibit ferromagnetic behavior at room temperature. The measured magnetization was strongly dependent on the Al content and reached a maximum for x=0.62. Previously reported photoluminescence measurements on these films yielded a blue emission at 465nm with peak intensity at the same Al content. Both magnetic and optical properties are directly correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…23 For such excitons, the emission energy is naturally associated with the optical band gap; but the peak energy of the 5 D 0 -7 F 2 transition is almost independent of the host composition: it decreases by only 7 meV between GaN and AlN. We note that a strikingly similar asymmetry of the magnetic moment of Al x Ga 1−x N:Tm has been recently reported by Nepal et al 24 Figure 5 compares PLE spectra of Al x Ga 1−x N:Eu samples, detected at the strongest peak of the 5 D 0 -7 F 2 luminescence apart from that for GaN, for which the longer wavelength peak at 622.5 nm was used to avoid mixing in of the second Eu component. The PLE spectra are normalized to the excitation peak at the band edge, except in the case of AlN, for which the band-edge onset near 200 nm ͑6.2 eV͒ is beyond reach of our excitation lamp.…”
Section: Resultssupporting
confidence: 86%
“…23 For such excitons, the emission energy is naturally associated with the optical band gap; but the peak energy of the 5 D 0 -7 F 2 transition is almost independent of the host composition: it decreases by only 7 meV between GaN and AlN. We note that a strikingly similar asymmetry of the magnetic moment of Al x Ga 1−x N:Tm has been recently reported by Nepal et al 24 Figure 5 compares PLE spectra of Al x Ga 1−x N:Eu samples, detected at the strongest peak of the 5 D 0 -7 F 2 luminescence apart from that for GaN, for which the longer wavelength peak at 622.5 nm was used to avoid mixing in of the second Eu component. The PLE spectra are normalized to the excitation peak at the band edge, except in the case of AlN, for which the band-edge onset near 200 nm ͑6.2 eV͒ is beyond reach of our excitation lamp.…”
Section: Resultssupporting
confidence: 86%
“…1 Similar magnetic properties, particularly the ferromagnetism above room temperature, has been reported by others not only in Gd-doped GaN layers (GaN:Gd) 2-4 but also in Eudoped GaN, 5 Tm-doped (Al,Ga)N (Ref. 6), as well as Gdimplanted GaN and AlN layers. [7][8][9] Interestingly, the effective magnetic moment per Gd ion was found to be larger in Gd implanted GaN layers than in GaN:Gd layers doped in situ and also observed to decrease upon annealing.…”
supporting
confidence: 70%
“…In addition to that, the effective magnetic moment per Gd ion was found to be as high as 4000 µ B compare to the magnetic moment of a Gd 3+ ion [1,2,3]. Later, similar effects were reported for Eu doped GaN, Tm doped (Al,Ga)N layers as well as Gd implanted GaN and AlN layers [4,5]. Later Mishra et al has reported that high density of defects being generated in GaN:Gd layers doped in situ [6].…”
Section: Introductionmentioning
confidence: 51%